Stuck in India: Punjabi temporary migrants of New Zealand - Brown Pulu, Teena; Mukhtar, Asim (Te Kaharoa, 2022)
Our paper reflects on creating a short documentary in 2021 centred around an online discussion, which the second author recorded with three Punjabi migrants. At the time of being interviewed, these migrants had New Zealand temporary work and study visas and were stuck in Punjab, India, for more than a year since the New Zealand government announced on 19 March 2020 the international border would be closed indefinitely due to Covid-19. The documentary research found that Punjabis stranded in their country of origin were imploring Punjabis in New Zealand to lobby to the New Zealand state to let them return. As a result, Auckland migrant groups were advocating for temporary migrants to be allowed back.